2021
DOI: 10.3389/fmolb.2021.741316
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Repurposing Disulfiram and Disulfiram Derivatives as Copper-Dependent Anticancer Agents

Abstract: Copper (Cu) plays a pivotal role in cancer progression by acting as a co-factor that regulates the activity of many enzymes and structural proteins in cancer cells. Therefore, Cu-based complexes have been investigated as novel anticancer metallodrugs and are considered as a complementary strategy for currently used platinum agents with undesirable general toxicity. Due to the high failure rate and increased cost of new drugs, there is a global drive towards the repositioning of known drugs for cancer treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 175 publications
(212 reference statements)
1
59
0
Order By: Relevance
“…(In fact, on a molar basis copper (II) ions are probably the most potent known inhibitors of CBS, with an IC 50 of approximately 300 nM [ 167 , 174 , 175 ]). Disulfiram has been shown to exert anticancer effects in various preclinical models, and several targets have been proposed to explain this effect [ [176] , [177] , [178] , [179] ]. In fact, disulfiram (alone, or in various combinations, including a combination with copper) is currently in several clinical cancer trials [ [176] , [177] , [178] , [179] ].…”
Section: Pharmacological Inhibition Of Cbs In Cancer Cells and Cancer...mentioning
confidence: 99%
See 1 more Smart Citation
“…(In fact, on a molar basis copper (II) ions are probably the most potent known inhibitors of CBS, with an IC 50 of approximately 300 nM [ 167 , 174 , 175 ]). Disulfiram has been shown to exert anticancer effects in various preclinical models, and several targets have been proposed to explain this effect [ [176] , [177] , [178] , [179] ]. In fact, disulfiram (alone, or in various combinations, including a combination with copper) is currently in several clinical cancer trials [ [176] , [177] , [178] , [179] ].…”
Section: Pharmacological Inhibition Of Cbs In Cancer Cells and Cancer...mentioning
confidence: 99%
“…Disulfiram has been shown to exert anticancer effects in various preclinical models, and several targets have been proposed to explain this effect [ [176] , [177] , [178] , [179] ]. In fact, disulfiram (alone, or in various combinations, including a combination with copper) is currently in several clinical cancer trials [ [176] , [177] , [178] , [179] ]. Thus, it is possible that disulfiram may be ultimately repurposed for cancer therapy, although the extent to which a CBS inhibitory effect contribute to its clinical anticancer action remains unclear.…”
Section: Pharmacological Inhibition Of Cbs In Cancer Cells and Cancer...mentioning
confidence: 99%
“…DSF is an FDA-approved aldehyde dehydrogenase inhibitor for the treatment of alcoholism, and it has been effectively used for over 60 years. DSF, however, possesses other biological activities and there is been growing attention in repurposing DSF as an anticancer agent (Ekinci et al, 2019;Kannappan et al, 2021). This interest arises from the low cost, high availability, safety profile, and anticancer activity of DSF.…”
Section: Copper Ionophoresmentioning
confidence: 99%
“…The mixture Cu-DSF has been tested as an adjuvant in combination with known chemotherapeutic drugs such as cisplatin, temozolomide, gemcitabine, doxorubicin, etc (Li H. et al, 2020). Mounting evidence has demonstrated that Cu-DSF can have several targets including ROS levels, the ubiquitinproteasome system (UPS), nuclear factor-kappa B (NF-κB), NPL4 (Chen et al, 2006;Skrott et al, 2017;Oliveri, 2020;Kannappan et al, 2021). Despite the excellent results of DSF in vitro and in vivo, clinical studies of DSF in patients with cancer were not successful.…”
Section: Copper Ionophoresmentioning
confidence: 99%
See 1 more Smart Citation